On blowup solutions for the mixed fractional Schrödinger equation of Choquard type. (November 2022) - Chergui, L.
Abstract: We investigate some mixed fractional nonlinear Schrödinger equation of Choquard type. In the subcritical energy case local well-posedness is obtained. Moreover, based on a suitable Virial type inequality we show a general criterion of global existence versus blow-up for mass super-critical solutions.